Life in the brine of Lunenburg, Germany: unveiling microorganisms associated with Zechstein salt deposits - Runzheimer, Katharina; Schwab, Laura; Engel, Denise; Schaudinn, Christoph; Laue, Michael; Rebrošová, Katarína; Beblo-Vranesevic, Kristina; Azizah, Muhaiminatul; Leuko, Stefan (Frontiers in Microbiology, 2025)
IntroductionThe presence of hypersaline brines on other planets and moons in the inner and outer Solar System has been well established. Hence, any theory of life on other planets must consider microorganisms adapted to high salt concentrations. The hypersaline brine from Lunenburg (Germany) with 302.25 g L−1 NaCl, originating from the remnants of the Zechstein Sea, has long been utilized to harvest salt, but potential microbial life in the brine had never been investigated.MethodsWe employed cultivation-based and -independent methods to characterize the microbial diversity, while also analyzing environmental parameters. Specifically, we performed V1/V2 and V3/V4 amplicon sequencing of environmental DNA and conducted haloarchaeal-focused cultivation and enrichments. Furthermore, we conducted whole-genome sequencing and analysis, Raman spectroscopy, electron and fluorescence microscopy, and compatible solute analysis on two isolates from the frequently cultivated genera Haloarcula and Halorubrum.ResultsOur findings proved the presence of a broad range of halophilic microorganisms, including sulfate-reducing bacteria, haloarchaea and yet-uncultivated microorganisms like Nanohaloarchaeota and Patescibacteria in the Lunenburg brine. Two haloarchaeal isolates were described in more detail, revealing the presence of bacterioruberin for oxidative stress protection, potential polyhydroxyalkanoates for energy storage, pleomorphic structures as well as ‘package-like aggregates’ as possible adaptations to extreme conditions. Distinct osmotic adaptation strategies and a low average isoelectric point of the isolates’ proteomes were identified.DiscussionOur research shows that the hypersaline brine from Lunenburg harbors a diverse microbial community and is an ideal and easily accessible testbed to search for yet-uncultivated microorganisms as well as novel microorganisms to use for astrobiological studies.